Response of Arabidopsis thaliana to Flooding with Physical Flow - Momoko Kaji; Kazuma Katano; Taufika Islam Anee; Hiroshi Nitta; Ryotaro Yamaji; Rio Shimizu; Shunsuke Shigaki; Hiroyuki Suzuki; Nobuhiro Suzuki (Plants)
Flooding causes severe yield losses worldwide, making it urgent to enhance crop tolerance to this stress. Since natural flooding often involves physical flow, we hypothesized that the effects of submergence on plants could change when combined with physical flow. In this study, we analyzed the growth and transcriptome of Arabidopsis thaliana exposed to submergence or flooding with physical flow. Plants exposed to flooding with physical flow had smaller rosette diameters, especially at faster flow rates. Transcriptome analysis revealed that “defense response” transcripts were highly up-regulated in response to flooding with physical flow. In addition, up-regulation of transcripts encoding ROS-producing enzymes, SA synthesis, JA synthesis, and ethylene signaling was more pronounced under flooding with physical flow when compared to submergence. Although H2O2 accumulation changed in response to submergence or flooding with physical flow, it did not lead to lipid peroxidation, suggesting a role for ROS as signaling molecules under these conditions. Multiple regression analysis indicated possible links between rosette diameter under flooding with physical flow and the expression of Rbohs and SA synthesis transcripts. These findings suggest that pathogen defense responses, regulated by SA and ROS signaling, play crucial roles in plant responses to flooding with physical flow.